PENGARUH PELATIHAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN TELEMARKETING DI PT ASURANSI ALLIANZ BUMI SERPONG DAMAI - Siti Sukaesih; Shela Indah Savitri (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to ascertain the partial and simultaneous effects of work training and remuneration on employee performance. quantitative research approach that makes use of questionnaires, observational data gathering methods, and literature analysis. using an 80-person sample size. Research findings: The calculated t value > t table or 13.220 > t table 1.664 and the sig value. 0.000 < sig value 5% (0.05) and the calculated t value > t table or 8.228 > t table 1.664 and the sig value. 0.000 < sig value 5% (0.05) were among the partial research results that demonstrated this. These findings suggest that PT. Allianz BSD Insurance telemarketing employees' performance is positively and significantly impacted by both training and compensation. In addition, the sig. 0.000 < sig value 5% (0.05) and the computed F value of 88.075 > F table 2.72 both show that pay and training combined have a favorable and substantial impact on the performance of telemarketing staff at PT. Allianz BSD Insurance.